2011
DOI: 10.1007/s00228-011-1151-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lansoprazole as a probe for assessing cytochrome P450 2C19 activity and genotype–phenotype correlation in childhood

Abstract: According to our results from a Turkish pediatric population, lansoprazole is a suitable probe drug for phenotyping CYP2C19. The CYP2C19*2 and *17 variants should be taken into consideration in predicting the clinical outcome of therapy with lansoprazole in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
2
30
0
1
Order By: Relevance
“…Aynacioglu et al, who found the PM frequency to be~1% [13], reported that the mutation responsible for the PM genotype was CYP2C19*2 and that there was no CYP2C19*3 in any of the individuals in the study. In another study, conducted by Gumus et al [24], the CYP2C19*2 frequency was 1.2% and the CYP2C19*3 variant was not detected [24]. In our study, in accordance with these studies, we found the CYP2C19*2 genotype frequency to be 19.9%, while the CYP2C19*3 and CYP2C19*4 genotypes were not detected.…”
Section: Discussionsupporting
confidence: 92%
“…Aynacioglu et al, who found the PM frequency to be~1% [13], reported that the mutation responsible for the PM genotype was CYP2C19*2 and that there was no CYP2C19*3 in any of the individuals in the study. In another study, conducted by Gumus et al [24], the CYP2C19*2 frequency was 1.2% and the CYP2C19*3 variant was not detected [24]. In our study, in accordance with these studies, we found the CYP2C19*2 genotype frequency to be 19.9%, while the CYP2C19*3 and CYP2C19*4 genotypes were not detected.…”
Section: Discussionsupporting
confidence: 92%
“…Activity is then increased throughout childhood and finally reverts to levels similar to that in adults by puberty [6]. Earlier studies in pediatrics suggested little effect of CYP2C19 variation on PPIs, however, recent data have supported the role of CYP2C19 genotype in PPI therapy similar to that in adulthood [28,29]. Whether the effect of genotype on CYP2C19 is the same as in adults depends on the developmental stage of CYP2C19.…”
Section: Ppi Mechanismsmentioning
confidence: 99%
“…For CYP2C19 phenotyping, LPZ might be a useful probe drug (Zhang et al 2011;Gumus et al 2011). The differences in the formulations and gastrointestinal situations might affect the absorption extent and rate of LPZ when using LPZ oral formulations.…”
Section: Discussionmentioning
confidence: 99%